Total Iron Absorption - TOSSOU, FÉLICIEN (My University, 2013)
iron biofortlficauon of pearl millet (Pennisetum glaucum) is a promising approach to combat iron deficiency (ID) in the millet-consuming communities of developing countries. To evaluate the potential of iron-biofortified millet to provide additional bioavailable iron compared with regular millet and post-harvest iron-fortified millet, an iron absorption study was conducted in 20 Beninese women with marginal iron status. Composite test meals consisting of millet paste based on z regular-iron, iron-biofortified, or post-harvest iron-fortified pearl millet flour accompanied by a leafy vegetable sauce or an okra sauce were fed as multiple meals for 5 d. Iron absorption was measured as erythrocyte incorporation of stable iron o isotopes. Fractional iron absorption from test meals based on regular-iron millet (7.5%) did not differ from iron-biofortified millet meals (7 5%; P = 1.0). resulting jn a higher quantity of total iron absorbed from the meals based on iron-biofortified m Z millet (1125 vs 527 ,ug; P < 0.0001). Fractional iron absorption from post-harvest iron-fortified millet meals (10.4%) was higher than from regular-iron and iron-biofortified millet meals (P < 0.05 and P < 0.01, respectively), resulting in a higher o quantity of total iron absorbed from the post-harvest iron-fortified millet meals (1500 #9,' P < 0.0001 and P < 0.05, respectively), Results indicate that consumption of iron-biofortified millet would double the amount of iron absorbed and, although fractional absorption of iron from biofortification is less than that from fortification, iron-biofortified millet should be highly effective in combatting ID in millet-consuming populations.
Keywords: Iron Biofortified composite meals